2019
DOI: 10.1038/s41592-019-0512-x
|View full text |Cite|
|
Sign up to set email alerts
|

An efficient auxin-inducible degron system with low basal degradation in human cells

Abstract: Auxin-inducible degron technology allows rapid and controlled protein depletion. However, basal degradation without auxin and inefficient auxin-inducible depletion have limited its utility. We have identified a potent auxin-inducible degron system composed of auxin receptor F-box protein AtAFB2 and short degron miniIAA7. The system showed minimal basal degradation and enabled rapid auxin-inducible depletion of endogenous human transmembrane, cytoplasmic and nuclear proteins in 1 h with robust functional phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
218
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(229 citation statements)
references
References 27 publications
9
218
2
Order By: Relevance
“…While we are optimistic that the use of the synthetic analog of auxin presented here will allow even more widespread utility of the AID system in the C. elegans research community, there are still some areas open to improvement for the technology. Recent reports in mammalian cell culture identified that AID-tagged proteins are depleted in an auxin-independent fashion in the presence of TIR1, relative to wild-type levels (Natsume et al 2016;Li et al 2019a;Sathyan et al 2019). We examined if this was also occurring in C. elegans strains in our laboratory expressing AID-tagged proteins and TIR1.…”
Section: Figurementioning
confidence: 89%
“…While we are optimistic that the use of the synthetic analog of auxin presented here will allow even more widespread utility of the AID system in the C. elegans research community, there are still some areas open to improvement for the technology. Recent reports in mammalian cell culture identified that AID-tagged proteins are depleted in an auxin-independent fashion in the presence of TIR1, relative to wild-type levels (Natsume et al 2016;Li et al 2019a;Sathyan et al 2019). We examined if this was also occurring in C. elegans strains in our laboratory expressing AID-tagged proteins and TIR1.…”
Section: Figurementioning
confidence: 89%
“…We assessed the basal (-IAA) level of AC9 AID protein, and found that AC9 AID levels are ~40% of the levels of AC9 tagged with only a 3xHA in the same OsTIR1-expressing parental line ( Figure S1). Such basal degradation has been uncovered as a common artifact of the AID system (30,31). Notably, AC9 AID (wtcomp) conoids were indistinguishable from the parental strain, suggesting that reduced AC9 protein levels may be driving the apparent defect in conoid ultrastructure (Figures 1, S1).…”
Section: Loss Of Ac9 Blocks Host Cell Invasion and Egress And Parasitmentioning
confidence: 96%
“…In systems were relative DNA dosages cannot be easily tuned, RNA aptazymes 41 and/or inducible protein degradation domains [42][43][44] could be used to independently tune output levels. To control multiple output genes, it will be possible to construct additional orthogonal iFFLs using our recently-described panel of endoRNases 32 .…”
Section: Our Results Show That Expression From Constitutive Promotersmentioning
confidence: 99%